Quantum error detection and correction - Wang, Yi (Nanyang Technological University, 2024)
Quantum device error rates are orders of magnitude greater than what is required to operate the majority of quantum applications. Quantum Error Correction (QEC) encapsulates logical qubits and distributes information using multiple physical qubits in order to improve this problem. In this dissertation, we propose a method to implement QEC based on Steane code, namely 5-qubit Stabilizer Scheme. 5 qubits consist of 3 data qubits and 2 ancilla qubits. By using this scheme, any single quantum bit error can be detected and corrected successfully. Unfortunately, with the gradual increase in the number of bits in a quantum device, one quantum bit error correction schemes are no longer sufficient. Therefore based on the original 5-qubit stabilizer scheme, the multiple-cycle scheme is proposed by measuring the ancilla qubit several times. It can simultaneously correct errors occurring in 3-bit data quantum bits.